2003
DOI: 10.1677/joe.0.1760305
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of T cell receptor rearrangement excision circles to estimate thymic function: an important new tool for endocrine-immune physiology

Abstract: Although the thymus constitutes a target organ for most protein and steroid hormones, it has been quite difficult to determine the precise control exerted in vivo by the endocrine system upon thymic function. The biological role of the thymus is to ensure the generation of a diversified population of peripheral T cells able to respond to non-self-antigens but nevertheless tolerant to selfantigens. For a long time, thymic function could not be monitored, as a consequence of the absence of adequate technology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 57 publications
11
45
0
4
Order By: Relevance
“…These findings support the view that the levels of WRN, BLM and RecQL1 helicases are crucial to guarantee genomic stability in actively proliferating and/or transformed cells [11]. Multiple experimental evidences suggested analogies of T cell dynamics between advanced ageing and HIV infection [19][20][21][22][23][24][25][26][27][28][29][30]. Recently, it has been suggested that through a process of continuous immune activation HIV-1 infection leads to an acceleration in the ageing process of the adaptive immune system, thus contributing to immunodeficiency [31].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings support the view that the levels of WRN, BLM and RecQL1 helicases are crucial to guarantee genomic stability in actively proliferating and/or transformed cells [11]. Multiple experimental evidences suggested analogies of T cell dynamics between advanced ageing and HIV infection [19][20][21][22][23][24][25][26][27][28][29][30]. Recently, it has been suggested that through a process of continuous immune activation HIV-1 infection leads to an acceleration in the ageing process of the adaptive immune system, thus contributing to immunodeficiency [31].…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, a decreasing number of recent thymic emigrants, identified as T cell receptor excision circles (TRECs) [27][28][29], have been observed with ageing and in HIVinfected individuals, while highly active antiretroviral therapy (HAART) treatment leads to an increased thymic output [29,30]. Therefore, there is a developing hypothesis that HIV-1 infection leads to an acceleration of the adaptive immune system ageing process, resulting in a premature exhaustion of immune resources and leading eventually to the onset of immunodeficiency [31].…”
Section: Introductionmentioning
confidence: 99%
“…The human thymus has its highest activity phase in an age group from 0-10 y and shows a major activity drop in the population older than 39 y. Nevertheless, the thymus remains still active in the elderly population (12,13).…”
Section: Nfluenza a Virus Infection Causes Severe Disease In Humansmentioning
confidence: 99%
“…As previously described, 13,21,22 parallel quantification of each TREC together with the CD3␥ chain (used as a housekeeping gene) was performed for each sample using the LightCycler technology (Roche Diagnostics, Mannheim, Germany). PBMCs were lysed in Tris (10 mM, pH 8.2) Tween-20 (0.05%), NP-40 (0.05%), and Proteinase K (100 g/mL) for 30 minutes at 56°C and then 15 minutes at 98°C.…”
Section: Trec Quantificationmentioning
confidence: 99%